3′-Processing and strand transfer catalysed by retroviral integrase in crystallo - Hare, Stephen (Nature Publishing Group, 2012)
Retroviral integrase (IN) is responsible for two consecutive reactions, which lead to insertion of a viral DNA copy into a host cell chromosome. Initially, the enzyme removes di- or trinucleotides from viral DNA ends to expose 3′-hydroxyls attached to the invariant CA dinucleotides (3′-processing reaction). Second, it inserts the processed 3′-viral DNA ends into host chromosomal DNA (strand transfer). Herein, we report a crystal structure of prototype foamy virus IN bound to viral DNA prior to 3′-processing. Furthermore, taking advantage of its dependence on divalent metal ion cofactors, we were able to freeze trap the viral enzyme in its ground states containing all the components necessary for 3′-processing or strand transfer. Our results shed light on the mechanics of retroviral DNA integration and explain why HIV IN strand transfer inhibitors are ineffective against the 3′-processing step of integration. The ground state structures moreover highlight a striking substrate mimicry utilized by the inhibitors in their binding to the IN active site and suggest ways to improve upon this clinically relevant class of small molecules.